2018
DOI: 10.30799/jnst.118.18040304
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium Oxide/Graphene Oxide Nanocomposites as Efficient Supercapacitor Electrodes

Abstract: This paper reports on the preparation of graphene oxide (GO) modified with hafnium oxide (HO) nanoparticles composites by a simple mixing and their use as efficient electrode in electrochemical supercapacitors. The technique relies on simple mixing the aqueous solutions of hafnium oxide (HO) nanoparticles and graphene oxide (GO) at different ratios of GO content (20, 30 and 40 wt%). The morphological studies, chemical composition and electrochemical behavior of the resulting HO/GO nanocomposites were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…HfO 2 ‐based nanoparticles have been reported to show antibacterial activity against certain Gram‐negative bacteria, such as Klebsiella pneumoniae and S. aureus . [ 66 ] Here, SHB nano‐HfO 2 showed moderate to high binding affinity toward each bacteria, with Pa_15442 and Pa_9027 showing the greatest adherence. Other studies have indicated the ability of HfO 2 nanopores/nanofilms to bind proteins and DNA, [ 8,67 ] implying that the fabricated HfO 2 –PDMS exhibited positively charged surface under the experimental conditions used and thus could have stimulated the bacterial adherence to this material.…”
Section: Discussionmentioning
confidence: 94%
“…HfO 2 ‐based nanoparticles have been reported to show antibacterial activity against certain Gram‐negative bacteria, such as Klebsiella pneumoniae and S. aureus . [ 66 ] Here, SHB nano‐HfO 2 showed moderate to high binding affinity toward each bacteria, with Pa_15442 and Pa_9027 showing the greatest adherence. Other studies have indicated the ability of HfO 2 nanopores/nanofilms to bind proteins and DNA, [ 8,67 ] implying that the fabricated HfO 2 –PDMS exhibited positively charged surface under the experimental conditions used and thus could have stimulated the bacterial adherence to this material.…”
Section: Discussionmentioning
confidence: 94%
“…However, the synthesized HfO2 NPs seem to exhibit poor monodispersity, which are not suitable for via i.v. injection [24][25][26]. Other the available preparation method for uniform HfO2 NPs are harsh, such as in the condition of anhydrous and anaerobic [27].…”
Section: Introductionmentioning
confidence: 99%
“…Like aforesaid series, hafnium oxide (HfO 2 ) is also one of the metal oxides in transition metals and it offers a lower cost, less toxic and its availability creates us more interest. Consequently, expectation of nanosized HfO 2 particles towards supercapacitor performance has increased [13] and addition of oxides can improve the cycling stability of energy storage devices (ESD) [14][15][16]. But, functionalization and dispersion of metal oxide are of crucial importance for their applications, as they have enormous utilization in several areas including defense, aerospace, electric vehicles and consumer electronics applications [17].…”
Section: Introductionmentioning
confidence: 99%